MAPPING GEOMORPHOLOGY AND TRAILS AROUND THE BIOLOGICAL STATION AT THE RESERVA BIOLOGICA ALBERTO BRENES (SIERRA DE TILARAN), COSTA RICA - Breckle, S.W.; Breckle, Rolf (Pensamiento Actual, 2012)
In thc last ycars several research projects werr started to elucidate structure, dynamics and diversity of the primary premontane forest at the Reserva Biológica Alberto Brenes (RBAB). The Biological Station steadily was improved and is more and more a very useful base for research in tropical ecology (Ortiz 1991).